2006
DOI: 10.1590/s0001-37652006000200008
|View full text |Cite
|
Sign up to set email alerts
|

Secretory organelles of pathogenic protozoa

Abstract: Secretory processes play an important role on the biology and life cycles of parasitic protozoa. This review focus on basic aspects, from a cell biology perspective, of the secretion of (a) micronemes, rhoptries and dense granules in members of the Apicomplexa group, where these organelles are involved in the process of protozoan penetration into the host cell, survival within the parasitophorous vacuole and subsequent egress from the host cell, (b) the Maurer's cleft in Plasmodium, a structure involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 123 publications
0
19
0
1
Order By: Relevance
“…In promastigotes, gold particle labeling showed the serine protease to be predominantly located in the flagellar pocket and in vesicular structures which are morphologically similar to the compartments found in mammalian endocytic/exocytic pathways (Figure 2 A and B). It is worth noting, as mentioned previously, that the flagellar pocket is a secluded extracellular compartment in the anterior portion of Leishmania formed by an invagination of the plasma membrane at the base of the flagellum and is the only part of the cell surface that supports exocytosis and endocytic traffic of molecules (De Souza, 2006;Bonhivers et al, 2008). This pocket is an obligatory intermediary station for membrane-bound molecules trafficking between intracellular membranes and the cell surface and vice-versa (Overath et al, 1997).…”
Section: Immunocytochemistry Of Proteases In the Study Of Leishmania mentioning
confidence: 82%
See 1 more Smart Citation
“…In promastigotes, gold particle labeling showed the serine protease to be predominantly located in the flagellar pocket and in vesicular structures which are morphologically similar to the compartments found in mammalian endocytic/exocytic pathways (Figure 2 A and B). It is worth noting, as mentioned previously, that the flagellar pocket is a secluded extracellular compartment in the anterior portion of Leishmania formed by an invagination of the plasma membrane at the base of the flagellum and is the only part of the cell surface that supports exocytosis and endocytic traffic of molecules (De Souza, 2006;Bonhivers et al, 2008). This pocket is an obligatory intermediary station for membrane-bound molecules trafficking between intracellular membranes and the cell surface and vice-versa (Overath et al, 1997).…”
Section: Immunocytochemistry Of Proteases In the Study Of Leishmania mentioning
confidence: 82%
“…Consistent with this observation, a low level secretion of this cysteine protease into the culture medium was detected (Duboise et al, 1994). It is known that the flagellar pocket is a secluded extracellular compartment in the anterior portion of trypanosomatids, formed by an invagination of the plasma membrane at the base of the flagellum and is the only part of the cell surface that supports exocytosis and endocytic traffic in Leishmania and other trypanosomatids because of its lack of attached microtubules (De Souza, 2006;Bonhivers et al, 2008). The flagellar pocket membrane is an obligatory intermediary station for membrane-bound molecules trafficking between intracellular membranes and the cell surface and vice-versa (Overath et al, 1997).…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…3,12 We and others 49 have shown that a single ookinete possesses numerous micronemes, corresponding to the most abundant, densely packed organelle found in the cell ( Figure 3A). These dense, protein-packed organelles are enclosed by a lipid membrane, 59 but whether all micronemes contain the same set of proteins is unknown. The large number of micronemes combined with the extraordinary constitutive secretory capacity of the ookinete suggests that any neutralizing antibodies targeting micronemal proteins may be needed in a very high titer for effective transmission blocking.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction takes place either by the direct participation of surface-associated components or by secretion, via portions of the cell surface, of components synthesized within the cell and released via secretory vesicles [3]. The surface of intracellular parasites, as is the case of Trypanosoma cruzi and Leishmania, interacts initially with the surface of the host cell of the vertebrate host and with the membrane of the parasitophorous vacuole.…”
Section: The Cell Surfacementioning
confidence: 99%
“…Figs. (1)(2)(3) show schematic views of representatives of trypanosomatids, apicomplexans and trichomonads, respectively.…”
Section: Introductionmentioning
confidence: 99%